1998
DOI: 10.1164/ajrccm.157.4.9705023
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Aerobic and Anaerobic Exercise Performance in Cystic Fibrosis

Abstract: We examined aerobic and anaerobic exercise performance in 17 subjects with cystic fibrosis (CF) (age 25+/-10 [SD] yr; 47% females; FEV1 62+/-21% pred) and 17 age- and sex-matched control subjects (age 25+/-8 [SD] yr; 41% females; FEV1 112+/-15% pred) in relation to pulmonary function and nutritional status. Aerobic capacity was determined as maximal oxygen consumption (VO2max) (ml/kg/min) and anaerobic threshold (AT; ml VO2/kg/min) from a graded exercise stress test on an electronically braked bicycle ergomete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
55
1
2

Year Published

2003
2003
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(64 citation statements)
references
References 23 publications
6
55
1
2
Order By: Relevance
“…Our research team has recently demonstrated the expression of CFTR in human skeletal muscle (7). In addition, evidence suggests that impaired anaerobic performance (8), abnormal anaerobic metabolism (9), and decreased maximal muscle strength and power (10 -12) occurs in CF patients. Recently, [ 31 P]phosphorus magnetic resonance spectroscopy ( 31 P-MRS) to assess muscle metabolism has been used in vivo (13,14) to assess the function of creatine kinase, oxidative phosphorylation, and anaerobic glycolysis pathways during exercise and recovery.…”
mentioning
confidence: 99%
“…Our research team has recently demonstrated the expression of CFTR in human skeletal muscle (7). In addition, evidence suggests that impaired anaerobic performance (8), abnormal anaerobic metabolism (9), and decreased maximal muscle strength and power (10 -12) occurs in CF patients. Recently, [ 31 P]phosphorus magnetic resonance spectroscopy ( 31 P-MRS) to assess muscle metabolism has been used in vivo (13,14) to assess the function of creatine kinase, oxidative phosphorylation, and anaerobic glycolysis pathways during exercise and recovery.…”
mentioning
confidence: 99%
“…Peak exercise performance is reduced in patients with CF [1][2][3][4][5][6][7][8][9][10]. Pulmonary function correlates with peak aerobic and anaerobic exercise capacity [8][9][10], and this relationship has been interpreted as indicating a pulmonary limitation to exercise in CF.…”
mentioning
confidence: 99%
“…Furthermore, exercise testing has been used as an outcome measure of therapy and exercise programmes, as well as for prognostic purposes (1)(2)(3)(4)(5)(6). It has been established, that aerobic and anaerobic capacity is reduced in most patients with CF when compared to their healthy counterparts, with impaired respiratory function and malnutrition being likely contributing factors (7)(8)(9)(10). It has also been documented that children with CF with higher activity levels have a better aerobic and anaerobic fitness and nutritional status, and a significantly lower disease severity (11).…”
Section: Exercise Testing In Cystic Fibrosis (Cf) Is Gaining Clinicalmentioning
confidence: 99%
“…There is little doubt that aerobic and anaerobic capacity is reduced in CF individuals, when compared to their healthy counterparts (7)(8)(9)(10). This reduction may be explained by an impaired lung function and malnutrition.…”
Section: Exercise Testing In Cystic Fibrosis (Cf) Is Gaining Clinicalmentioning
confidence: 99%